Pengaruh Pelatihan K3 dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. Central Panganpertiwi - Eva Nurfadillah; Budi Rismayadi; Wike Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the influence of occupational health and safety (OHS) training and the work environment on employee performance at PT. Central Panganpertiwi. This research was conducted by applying quantitative techniques through a descriptive-verification approach. Data collection was carried out by distributing questionnaires to 60 employees selected using simple random sampling. The results of multiple linear regression analysis stated that OHS training significantly impacted employee performance with a regression coefficient value = 0.293 and a significance value = 0.016. The work environment also significantly influences performance, with a regression coefficient of 0.468 and a significance value of <0.001. Simultaneously, these variables contribute 72.8% to improving employee performance. The study concludes the importance of enhancing the quality of OHS training through more in-depth materials and interactive methods and improving the work environment, such as layout and lighting. The implications of this research can help companies increase productivity through better training programs and work environments and encourage further studies on other factors influencing performance.